Designing for patient risk assessment in primary health care: a case study for ergonomic work analysis. Issue 1 (February 2016) - Jatobá, Alessandro; Bellas, Hugo; Bonfatti, Renato; Burns, Catherine; Vidal, Mario; Carvalho, Paulo
Abstract In this paper, we study the importance of a consistent description of real work in patient risk assessment in the primary healthcare domain. Through a case study in the context of primary health care, we address the research problem of finding ways to build consistent real work descriptions of the patient risk assessment system in the primary healthcare domain, in order to foster the design of improved work situations and support devices. This is a qualitative field study based on ethnographic observation and semi-structured interviews carried out among professionals involved in the risk assessment process in a primary healthcare facility. The objects of ergonomic work analysis were work places and work situations with focus on human activity, as well as surrounding aspects. The analysis identified elements in the work domain with high cognitive demand and operations that could increase mental workload, providing elements for the earlier stages of the design of work situations and support devices to improve the risk assessment in primary health care. This paper shows the usefulness of real work descriptions in the design for complex situations like the risk assessment in health care, as well the impact of poor descriptions in generating harmful situations for both the patient and healthcare practitioners in the explored domain.